The impact of credit supply shocks in the euro area: Market-based financing versus loans - Kristina Barauskaite; Anh D. M. Nguyen; Linda Rousová; Lorenzo Cappiello (European Central Bank (ECB), 2022)
Using a novel quarterly dataset on debt financing of non-financial corporations, this paper provides the first empirical evaluation of the relative importance of loan and market-based finance (MBF) supply shocks on business cycles in the euro area as a whole and in its five largest countries. In a Bayesian VAR framework, the two credit supply shocks are identified via sign and inequality restrictions. The results suggest that both loan supply and MBF supply play an important role for business cycles. For the euro area, the explanatory power of the two credit supply shocks for GDP growth variations is comparable. However, there is heterogeneity across countries. In particular, in Germany and France, the explanatory power of MBF supply shocks exceeds that of loan supply shocks. Since MBF is mostly provided by non-bank financial intermediaries, the findings suggest that strengthening their resilience | such as through an enhanced macroprudential framework | would support GDP growth.
Keywords: C32; E32; E44; E51; G2; 330; debt securities; loan; credit supply; VAR; business cycles; non-bank nancialintermediation